Outcomes of Meaningful Work: A Meta‐Analysis - Allan, Blake A.; Batz-Barbarich, Cassondra; Sterling, Haley M.; Tay, Louis (Journal of Management Studies, 2019)
AbstractUsing job characteristics theory as a framework, we calculated meta‐analytic effect sizes between meaningful work and various outcomes and tested a mediated model of meaningful work predicting proximal and distal outcomes with meta‐analytic structural equation modelling (MASEM). From 44 articles (N = 23,144), we found that meaningful work had large correlations (r = 0.70+) with work engagement, commitment, and job satisfaction; moderate to large correlations (r = 0.44 to −0.49) with life satisfaction, life meaning, general health, and withdrawal intentions; and small to moderate correlations (r = −0.19 to 0.33) with organizational citizenship behaviours, self‐rated job performance, and negative affect. The best MASEM fitting model was meaningful work predicting work engagement, commitment, and job satisfaction and these variables subsequently predicting self‐rated performance, organizational citizenship behaviours, and withdrawal intentions. This meta‐analysis provides estimated effect sizes between meaningful work and its outcomes and reveals how meaningful work relates directly and indirectly to key outcomes.